Are national university systems becoming more alike? Long-term developments in staff composition across five countries. Issue 1 (2nd January 2020) - Stage, Andreas Kjær
ABSTRACT: National university systems have traditionally been characterised by major differences in both internal structures and external conditions. However, the global rise of the knowledge economy has made external conditions of universities more similar across countries. This paper investigates to what extent this convergence has been mirrored within the universities by systematically comparing staff changes over more than a decade in five countries: The United States, the United Kingdom, Germany, Norway, and Denmark. Measures of staff changes are partial but tangible indicators, which are reasonably comparable across countries and over time. The empirical analysis isolates and examines two parallel staff trends, which the higher education literature currently highlights as crucial for ongoing university transformations: Proliferation of temporary academic staff and professionalisation of administrative/managerial staff. In doing so, the analysis provides a tangible empirical basis for assessing the impact of global trends on historically distinct university systems. Staff compositions have changed in the same direction, but from different starting points and with different intensity. Staff changes have been larger in Europe than in the US, but not in ways erasing major historical differences. The directional similarity rather suggests that dissimilar universities have added a similar layer of certain types of human resources.